Close correlation of copy number aberrations detected by next‐generation sequencing with results from routine cytogenetics in acute myeloid leukemia. Issue 7 (2nd May 2016) - Vosberg, Sebastian; Herold, Tobias; Hartmann, Luise; Neumann, Martin; Opatz, Sabrina; Metzeler, Klaus H.; Schneider, Stephanie; Graf, Alexander; Krebs, Stefan; Blum, Helmut; Baldus, Claudia D.; Hiddemann, Wolfgang; et al.
Abstract : High throughput sequencing approaches, including the analysis of exomes or gene panels, are widely used and established to detect tumor‐specific sequence variants such as point mutations or small insertions/deletions. Beyond single nucleotide resolution, sequencing data also contain information on changes in sequence coverage between samples and thus allow the detection of somatic copy number alterations (CNAs) representing gain or loss of genomic material in tumor cells arising from aneuploidy, amplifications, or deletions. To test the feasibility of CNA detection in sequencing data we analyzed the exomes of 25 paired leukemia/remission samples from acute myeloid leukemia (AML) patients with well‐defined chromosomal aberrations, detected by conventional chromosomal analysis and/or molecular cytogenetics assays. Thereby, we were able to confirm chromosomal aberrations including trisomies, monosomies, and partial chromosomal deletions in 20 out of 25 samples. Comparison of CNA detection using exome, custom gene panel, and SNP array analysis showed equivalent results in five patients with variable clone size. Gene panel analysis of AML samples without matched germline control samples resulted in confirmation of cytogenetic findings in 18 out of 22 cases. In all cases with discordant findings, small clone size (<33%) was limiting for CNA detection. We detected CNAs consistent with cytogenetics in 83% of AML samples including highly correlated clone size estimation ( R = 0.85), while six out of 65 cytogenetically normal AML samples exhibited CNAs apparently missed by routine cytogenetics. Overall, our results show that high throughput targeted sequencing data can be reliably used to detect copy number changes in the dominant AML clone. © 2016 Wiley Periodicals, Inc.